2019
DOI: 10.1002/jcb.29125
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating DDX3 expression by serotonin 5‐HT receptor 7 through phosphorylation of p53 via the AC‐PKA‐ERK signaling pathway

Abstract: DDX3 is a host viral factor that can inhibit the hepatitis B virus‐induced innate immune responses. In this study, the 20 bioactive compounds have screened the effects on DDX3 and we found that 5‐HT upregulated DDX3 promoter activity via the 5‐HT7 receptor on liver hepatocellular cells (HepG2 cells) by using a luciferase assay, reverse transcription‐polymerase chain reaction analysis, and Western blot analysis. Furthermore, we are trying to elucidate the pathways involved in the stimulating effect of 5‐HT on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Actually, ATP-dependent RNA helicase DDX3X appeared to be modulated by several compounds and cytokines via direct and/or indirect interactions. In liver hepatocellular cells, previous findings indicated that 5-HT treatment could augment 5-HT receptor 7-mediated DDX3X promoter activity as well as the induction of an innate immunity to abolish hepatitis B virus (HBV) infection [ 27 ]. Another research finding in hepatocellular HepG2 cells demonstrated that the addition of tazemetostat, SP2509, decitabine and trichostatin A led to the downregulation of DDX3X RNA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, ATP-dependent RNA helicase DDX3X appeared to be modulated by several compounds and cytokines via direct and/or indirect interactions. In liver hepatocellular cells, previous findings indicated that 5-HT treatment could augment 5-HT receptor 7-mediated DDX3X promoter activity as well as the induction of an innate immunity to abolish hepatitis B virus (HBV) infection [ 27 ]. Another research finding in hepatocellular HepG2 cells demonstrated that the addition of tazemetostat, SP2509, decitabine and trichostatin A led to the downregulation of DDX3X RNA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al confirmed that the activation of 5-HTR 7 by 5-HT stimulated the expression of DDX3 through adenylate cyclase (AC)/protein kinase A (PKA)/extracellular regulated protein kinases (ERK)-mediated phosphorylation of p53, thereby inhibiting HBV replication. These findings highlight the potential of targeting 5-HTR 7 as a strategy to suppress HBV infection [ 9 ].…”
Section: -Ht In Viral Hepatitismentioning
confidence: 99%
“…However, since the 21st century, there has been an increasing exploration of the role of 5-HT in liver diseases. From hepatitis [ 9 ], fatty liver [ 10 ] and acute liver injury [ 11 ] to cirrhosis [ 12 ] and liver cancer [ 13 ], the involvement of 5-HT has been identified as a significant and noteworthy contribution. However, the role of 5-HT in the liver is complex and seems contradictory, as it has the potential to both promote hepatic regeneration and accelerate tumor growth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human monocyte-derived macrophages, the IL-1β, LPS-and TNF-α-dependent NF-κB, and JNK signaling pathways were blocked by Zc3h12a [67]. In liver hepatocellular cells, 5-HT treatment increased 5-HT receptor 7-dependent DDX3X promoter activity, along with downstream expression, to induce innate immunity against hepatitis B virus (HBV) infection [68]. Activation of innate immune response through the TBK1/IKKε/IRF3 signaling axis was also observed by the ginsenoside Rg3 stimulus, which increased Akt-p53-dependent DD3X promoter transactivation and its expression level [69].…”
Section: Ddx3x Modulations By Cytokines and Compoundsmentioning
confidence: 99%